2012
DOI: 10.2169/internalmedicine.51.7132
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Development of Acute Disseminated Encephalomyelitis and Guillain-Barré Syndrome Associated with H1N1 09 Influenza Vaccination

Abstract: A 36-year-old man was admitted to our hospital because of urinary retention and muscle weakness affecting all 4 limbs after receiving a H1N1 09 influenza vaccination. Magnetic resonance imaging demonstrated multiple lesions in his brain and spinal cord. Furthermore, nerve conduction study showed acute sensorimotor neuropathy, and anti-GM2 antibodies were detected in his serum. Based on the temporal association and exclusion of alternative etiologies, we made a diagnosis of acute disseminated encephalomyelitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 20 publications
1
12
0
Order By: Relevance
“…Complications following H1N1 infection may occur and the most common are those involving the respiratory tract. Neurological complications may be seen in up 10% of children with H1N1 infection the most common include acute disseminated encephalomyelitis (ADEM), acute necrotizing encephalitis (ANEC), influenza encephalitis, and Guillain-Barré syndrome have also been described 13,15,16,17,18,19 . H1N1 vaccination is an important prophylatic tool to decrease the incidence, intensity, and morbidity of the disease 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Complications following H1N1 infection may occur and the most common are those involving the respiratory tract. Neurological complications may be seen in up 10% of children with H1N1 infection the most common include acute disseminated encephalomyelitis (ADEM), acute necrotizing encephalitis (ANEC), influenza encephalitis, and Guillain-Barré syndrome have also been described 13,15,16,17,18,19 . H1N1 vaccination is an important prophylatic tool to decrease the incidence, intensity, and morbidity of the disease 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Laski et al [27] recorded a 2% of increase of GBS cases per million vaccinated persons and also in the influenza vaccination program (1992)(1993). Hoshino et al (2012) reported the first clinical case of acute disseminated encephalomyelitis (ADEM) and GBS associated to H1N1 vaccination in a 36-year-old man [42]. The man developed acute urinary retention, weakness, limbs numbness, and difficulty in walking within 10 days after the vaccine inoculation.…”
Section: Influenza Vaccine and Guillain-barre Syndromementioning
confidence: 99%
“…These results suggest a multiinfectious etiology of GBS or an increased susceptibility of GBS patients to infection, supposing that GBS is probably both a humoral and a cellular autoimmune disease induced by infection with multiple microorganisms [45]. Several mechanisms might explain this outcome: (1) The epitopes of a vaccine could initiate the development of antibodies and/or T cells that could cross-react with epitopes on myelin or axonal glycoproteins; (2) Destruction of the axonal or myelin membranes might be due directly by vaccine virus or vaccine-associated products; (3) Possible genetic susceptibility [42,46,47] might be the background. To date, there are no epidemiologic studies that address the question of the risk of GBS development after vaccination, delaying immunization for a short period (e.g., one year) in all the patients with a previous neurological illness is recommended bring some risk (especially after tetanus toxoid) [48].…”
Section: Influenza Vaccine and Guillain-barre Syndromementioning
confidence: 99%
“…The major mechanism resulting in the autoimmunity by adjuvant vaccinations has been proposed to be due to the epitopes of a vaccine that initiates the development of antibodies and/or T cells that could cross-react with epitopes on myelin or axonal glycoproteins [16]. This was the same mechanism that was seen in the remnant sample of the 1976 swine flu sample where antibodies to the ganglioside GM1 was not detected in subjects infected with or vaccinated against the H1N1 virus [17], but they were detected in a patient who developed GBS associated with the pandemic influenza vaccine [18]. There were far fewer cases reported with GBS development after administration of the pneumococcal vaccine however.…”
Section: Gbs Is Commonly Linked To Different Infections Particularlymentioning
confidence: 86%